PENERAPAN MODEL PEMBELAJARAN PJBL UNTUK MENINGKATKAN HASIL BELAJAR PADA KOMPETENSI PENATAAN SANGGUL MODERN FREESTYLE WAVE KELAS XII DI SMK NEGERI 1 SOOKO - Aurellia Puspa Nathasya Wigatty; Octaverina Kecvara Pritasari; Sri Usodoningtyas; Novia Restu Windayani (Program Studi Pendidikan Tata Rias, 2026)
This study aims to determine the implementation of Project-Based Learning (PjBL), improvements in students’ learning outcomes in cognitive and psychomotor aspects, and students’ responses to the application of the PjBL model. The study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The study sample consisted of 32 twelfth-grade students in the Skin and Hair Care (TKKR) program at SMK Negeri 1 Sooko Mojokerto, selected using saturation sampling. Data collection was conducted through observation, tests, and questionnaires. The data were analyzed descriptively, while improvements in learning outcomes were analyzed using the Shapiro-Wilk normality test and the paired-sample t-test. The results of the study indicate that the implementation of the PjBL syntax fell into the “very well implemented” category, with an increase in the average score from 4.00 to 4.43. Cognitive learning outcomes improved significantly, as evidenced by an increase in the number of students achieving mastery from 6 to 31, as well as the results of the paired-sample t-test, which showed a Sig. (2-tailed) value of 0.000 (<0.05). In the psychomotor aspect, students achieved an average score of 90, falling into the “very good” category. Student responses to the implementation of PjBL also fell into the “very good” category, with a percentage of 98%. Thus, the PjBL model is effective in improving the implementation of instruction, cognitive and psychomotor learning outcomes, and in eliciting positive responses from students regarding the competency in Modern Freestyle Wave Hair Styling.